Effectiveness of uncoated WC-Co and PCD inserts in end milling of aluminum silicon carbide (AlSiC) - M. K., Nor Khairusshima; Amin, A. K. M. Nurul; Ismail, Ahmad Faris (Elsevier, 2007)

(untitled)
Metal matrix composite (MMC) with silicon carbide (SiC) reinforcement in pure aluminum matrix have found wide application in the automotive industry, especially in fiber reinforced pistons and particle-strengthened brake discs. Silicon carbide (SiC) reinforcement provides improved mechanical properties, thermal stability, high temperature formability and workability. However, the presence of the SiC phase in the structure causes serious machinability problems, especially when uncoated and coated WC-Co tools are used for their machining. High intensity of wear is attributed to high abrasive wear caused by the hard silicon carbide particles. In the current work investigations have been conducted to compare the performance of PCD tools with the conventional uncoated tungsten carbide-cobalt tool in machining aluminum silicon carbide (AlSiC) in terms of the applicable cutting speed ranges; chip morphology, tool wear rates and tool wear morphology, volume of metal removal allowed per tool life and attainable surface roughness.